1992
DOI: 10.1038/hdy.1992.129
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in elytral colour polymorphism in Harmonia axyridis (the ladybird beetle): the role of non-random mating

Abstract: Seasonal variation in the frequency of elytral colour polymorphism in the ladybird beetle, Harmonia axyridis, was analysed through the combination of field observations and laboratory mate-choice experiments. Field observations involving daily mark-recapture of a local population revealed an overall preponderance of melanie morphs in the population, but the proportion of nonmelanics notably increased from spring to summer due to their higher frequency of mating among different morphs of the spring generation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 35 publications
2
88
1
2
Order By: Relevance
“…Forms succinea, conspicua and spectabilis (according Osawa & Nishida, 1992;Mitchie et al, 2010) were found over the sampling period. The form succinea was the prevalent over the whole period and represented between 73 to 81% of the individuals (Fig.…”
Section: Overwintering Sitesmentioning
confidence: 99%
“…Forms succinea, conspicua and spectabilis (according Osawa & Nishida, 1992;Mitchie et al, 2010) were found over the sampling period. The form succinea was the prevalent over the whole period and represented between 73 to 81% of the individuals (Fig.…”
Section: Overwintering Sitesmentioning
confidence: 99%
“…Many modifications, such as elytral patterns, body shape and body size may be adaptive through imparting increased tolerance to adverse conditions (Dobzhansky 1933;Soares et al 2003a). The relative frequency of phenotypes seems to be related to geographical and seasonal factors (Tan 1946(Tan , 1949Komai 1956;Iablokoff-Khnzorian 1982;Osawa and Nishida 1992), suggesting that some phenotypes may be favorably selected in different parts of the ecosystem or at different times. Thus the genetic polymorphism in H. axyridis seems to be the strategy adopted for facing different habitats at different times.…”
Section: Harmonia Axyridis: a Super Invader?mentioning
confidence: 99%
“…Another factor might be a difference in the activity of the males of different forms. Osawa & Nishida (1992) studied mating preference in a Kyoto population of the polymorphic Asian species, H. axyridis. In this population, there occur three melanic forms (axyridis, spectabilis and conspicua) and one nonmelanic form (succinea).…”
Section: Preferential Mating In Adalia Bipunctatamentioning
confidence: 99%